Adult and Continuing Education in Norway - Bjerkaker, Sturla (W. Bertelsmann Verlag, 2016)
The European arena of lifelong learning offers rich country-specific portfolios of historical trajectories, policy frameworks and practical evidence of adult and continuing education. This book provides an introduction to the case of Norway and outlines the key features of the Norwegian system alongside issues such as political and legal agendas, schemes of participation, provision and financing or trends in professionalization, research areas and transnational linkages. Through the lens of adult and continuing education, the author invites researchers, practitioners, students and persons interested in international-comparative perspectives to a tour d'horizon of the Norwegian lifelong learning landscape.
Description based on print version record.
KU Open Services
Keywords: Education / Adult & Continuing Education; Education; Electronic books